The monodominant species Spirotropis longifolia is mainly nodulated by strains of the genus Bradyrhizobium outside the B. japonicum and B. elkanii superclades - Christine Le Roux; Emile Fonty; Laurent Brottier; Mathilde Bernard; Yves Prin; Daniel Sabatier (Symbiosis, 2024)

Mediterranean forests, land use and climate change: a social-ecological perspective - Thierry Gauquelin; Geneviève Michon; Richard Joffre; Robin Duponnois; Didier Génin; Bruno Fady; Magda Bou Dagher-Kharrat; Arezki Derridj; Said Slimani; Wadi Badri; Mohamed Alifriqui; Laurent Auclair; et al. (Regional Environmental Change, 2018)

Ectomycorrhizal fungal diversity associated with endemic Tristaniopsis spp. (Myrtaceae) in ultramafic and volcano-sedimentary soils in New Caledonia - Muhammad Waseem; Marc Ducousso; Yves Prin; Odile Domergue; Laure Hannibal; Clarisse Majorel; Philippe Jourand; Antoine Galiana (Mycorrhiza, 2017)

Multivariate analyses in soil microbial ecology: a new paradigm - Jean Thioulouse; Yves Prin; Robin Duponnois (Environmental and Ecological Statistics, 2012)

Monoxenic nodulation process of Acacia mangium (Mimosoideae, Phyllodineae) by Bradyrhizobium sp - Marie-Mathilde Perrineau; Antoine Galiana; Sergio M. de Faria; Gilles Bena; Robin Duponnois; Paul Reddell; Yves Prin (Symbiosis, 2012)

Response of native soil microbial functions to the controlled mycorrhization of an exotic tree legume, Acacia holosericea in a Sahelian ecosystem - Ablasse Bilgo; Sheikh K. Sangare; Jean Thioulouse; Yves Prin; Victor Hien; Antoine Galiana; Ezekeil Baudoin; Mohamed Hafidi; Amadou M. Bâ; Robin Duponnois (Mycorrhiza, 2012)

Soil factors influencing the growth response of Acacia holosericea A. Cunn. ex G. Don to ectomycorrhizal inoculation - Robin Duponnois; Marija Kisa; Yves Prin; Marc Ducousso; Christian Plenchette; Michel Lepage; Antoine Galiana (New Forests, 2008)

Arbuscular mycorrhizas and ectomycorrhizas of Uapaca bojeri L. (Euphorbiaceae): sporophore diversity, patterns of root colonization, and effects on seedling growth and soil microbial catabolic diversity - Naina Ramanankierana; Marc Ducousso; Nirina Rakotoarimanga; Yves Prin; Jean Thioulouse; Emile Randrianjohany; Luciano Ramaroson; Marija Kisa; Antoine Galiana; Robin Duponnois (Mycorrhiza, 2007)

Co-inoculation of Acacia mangium with Glomus intraradices and Bradyrhizobium sp. in aeroponic culture - Jean Weber; Marc Ducousso; Foong Yee Tham; Sophie Nourissier-Mountou; Antoine Galiana; Yves Prin; Sing Kong Lee (Biology and Fertility of Soils, 2005)

Co‐evolution between Frankia populations and host plants in the family Casuarinaceae and consequent patterns of global dispersal - Pascal Simonet; Elisabeth Navarro; Carole Rouvier; Paul Reddell; Jeff Zimpfer; Yvon Dommergues; René Bardin; Pilar Combarro; Jérôme Hamelin; Anne‐Marie Domenach; François Gourbière; Yves Prin; et al. (Environmental Microbiology, 1999)
Symbioses between the root nodule‐forming, nitrogen‐fixing actinomycete Frankia and its angiospermous host plants are important in the nitrogen economies of numerous terrestrial ecosystems. Molecular characterization of Frankia strains using polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP) analyses of the 16S rRNA‐ITS gene and of the nif D– nif K spacer was conducted directly on root nodules collected worldwide from Casuarina and Allocasuarina trees. In their native habitats in Australia, host species contained seven distinctive sets of Frankia in seven different molecular phylogenetic groups. Where Casuarina and Allocasuarina trees are newly planted outside Australia, they do not normally nodulate unless Frankia is introduced with the host seedling. Nodules from Casuarina trees introduced outside Australia over the last two centuries were found to contain Frankia from only one of the seven phylogenetic groups associated with the host genus Casuarina in Australia. The phylogenetic group of Frankia found in Casuarina and Allocasuarina trees introduced outside Australia is the only group that has yielded isolates in pure culture, suggesting a greater ability to survive independently of a host. Furthermore, the Frankia species in this group are able to nodulate a wider range of host species than those in the other six groups. In baiting studies, Casuarina spp. are compatible with more Frankia microsymbiont groups than Allocasuarina host spp. adapted to drier soil conditions, and C. equisetifolia has broader microsymbiont compatibility than other Casuarina spp. Some Frankia associated with the nodular rhizosphere and rhizoplan, but not with the nodular tissue, of Australian hosts were able to nodulate cosmopolitan Myrica plants that have broad microsymbiont compatibility and, hence, are a potential host of Casuarinaceae‐infective Frankia outside the hosts' native range. The results are consistent with the idea that Frankia symbiotic promiscuity and ease of isolation on organic substrates, suggesting saprophytic potential, are associated with increased microsymbiont ability to disperse and adapt to diverse new environments, and that both genetics and environment determine a host's nodular microsymbiont.